2002
DOI: 10.1021/ol0200807
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of (−)-Adaline

Abstract: [reaction: see text] An enantioselective total synthesis of (-)-adaline has been achieved starting from a chiral 6,6-disubstituted piperidone derivative previously prepared by diastereoselective allylation of a chiral tricyclic N-acyl-N,O-acetal. The key steps include lithium ion-activated SN2-type alkynylation of the tricyclic N,O-acetal leading to exclusive formation of the (6S)-ethynylpiperidine and ring-closing olefin metathesis of the (2R,6S)-cis-2,6-dialkenylpiperidine for constructing the bridged azabic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Amphidinolide A was synthesized by Maleczka group [48] using RCM reaction with high stereoselectivity. Substrate 54 did not give the desired product with catalyst A, but with catalyst B gave the desired product solely in E configuration (Scheme 16).…”
Section: Synthesis Of Oxygen Heterocyclesmentioning
confidence: 99%
“…Amphidinolide A was synthesized by Maleczka group [48] using RCM reaction with high stereoselectivity. Substrate 54 did not give the desired product with catalyst A, but with catalyst B gave the desired product solely in E configuration (Scheme 16).…”
Section: Synthesis Of Oxygen Heterocyclesmentioning
confidence: 99%
“…Kibayashi and co-workers have recently described an asymmetric synthesis of (À)-adaline 7 in which RCM was used to afford a [3.3.1] azabicyclic ring system (Scheme 2) [6]. It was found that the hydrochloride salt 8 was unable to induce the same conformational control as a N-acyl group.…”
Section: Bicyclic Ring Systemsmentioning
confidence: 99%
“…These systems possess added aryl groups fused to the interior of helical structure. Both protocols were found to be quite efficient for the formation of [6,7] required 60 min of microwave irradiation with 6 to undergo complete conversion to [7] helicene (81% isolated yield). Milder conditions with catalyst 34 also produced a 80% isolated yield of [7] helicene.…”
Section: Sterically Demanding Aromatic Ring Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…85) for total synthesis of lentiginosine [279]; (7) formation of tetrahydropyridine derivatives [280,281]; (8) asymmetric formation of tetrahydropyridine derivatives [282]; (9) formation of tetrahydropyridine derivatives for total synthesis of aspidosperma alkaloids [283]; (10) formation of 9-azabicyclo[3.3.1]nonane derivatives (e.g. 86) for total synthesis of adaline [284]; (11) formation of methylenedihydropyridines (e.g. 88) via RCM of a conjugated diene with a remote alkene [285]; (12) formation of bicyclic ␦-lactams (e.g.…”
Section: Ring Closing Metathesismentioning
confidence: 99%